Tailoring Supports to Youth in Schools: One Approach to Identifying Needs and Targeting Intervention - Tasha Henderson; Samantha Bates; Dawn Anderson-Butcher; Anthony Amorose; Erica Magier; Tarkington Newman (International Journal of School Social Work, 2020)
Youth experiences intersect along their race, gender, language and socioeconomic status, schools must consider the intersectionality in order to improve outcomes. The current study sought to understand if, and to what extent, different clusters of youth in one large urban high school perceive their psychosocial behaviors as well as social and interpersonal skills. Cross-sectional survey data from 1,164 high school youth were collected using four valid scales: Internalizing Behaviors, Externalizing Behaviors, Peer Relationships, and Social Skills. The analytic strategy was twofold. Cluster analysis was used to form homogeneous clusters of the 1,147 complete responses based on a combination of race/ethnicity, socioeconomic status, English language learner status, and gender. Next, a multivariate analysis of variance (MANCOVA) was used to compare cluster profiles on the aforementioned measures. The cluster analysis revealed a 5-factor solution. Findings of the MANCOVA showed that the clusters differed significantly on the set of psychosocial behaviors, social skills, and peer relationships variables (p<0.05, η2= 0.08), with significant univariate differences (p < 0.05) emerging on all four variables. Results point to cluster analysis as an emerging way to identify needs and tailor supports to youth in schools. Youth with identified needs could receive more specialized Tier II and III interventions aligned with their intersecting cultural and personal experiences, in addition to universal interventions to meet school wide priorities.
Keywords: schools; school-based intervention; high school; psychosocial behaviors